Skeletal anatomical description of Isogomphodon oxyrhynchus (Müller & Henle, 1839) and discussion of its phylogenetic position within Carcharhinidae (Chondrichthyes, Carcharhiniformes) - Silva, Arthur de Lima Oliveira e (2021)
The Daggernose shark Isogomphodon oxyrhynchus (Müller & Henle, 1839), sole species in its genus, is endemic to northern South America, from Southern Maranhão State in Brazil to Trinidad and Tobago. Although the species is traditionally classified as estuarine, it occurs also in entirely marine environments. Such habitat shift is seasonal, related to the rain regimen. I. oxyrhynchus is easily recognized by the elongated snout, enlarged pectoral fins and reduced eyes, characteristics which account for its unique general aspect in the family Carcharhinidae. The anatomy of I. oxyrhynchus remains poorly known and its phylogenetic position is still controversial. In this study, we propose a contribution to the knowledge of I. oxyrhynchus, offering: 1. A description of the entire skeleton and dermal denticles, based on dissections, computerized tomography and Scanning Electron Microscopy; 2. A comparative anatomical study of I. oxyrhynchus with other representatives of Carcharhinidae, which is compared with results from a novel molecular analysis; 3. Review of fossil taxa assigned to Isogomphodon. The skeletal description revealed much new information for I. oxyrhynchus, including new information on complexes which were previously entirely unknown in the taxon, such as the appendicular skeleton, mandibular arch and clasper. The comparative and phylogenetic study is organized into 46 morphological characters, which qualitatively supports Carcharhinus porosus as sister-group of I. oxyrhynchus. Results also support the hypothesis of Isogomphodon as a modified member of the genus Carcharhinus. Lastly, a critical review of the fossil taxa assigned to Isogomphodon demonstrated that from the five species previously assigned to Isogomphodon, only two can be positively attributed to the genus.